PENGARUH PERPUTARAN MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS [Studi Pada Perusahaan Food and Beverages yang Terdaftar di BEI Periode 2020-2022] - Riyadi, Wulan; Ahmad, Eva Fauziah; Hernita, Nita; Dewi, Dea Febrianti; Melia Wida Rahmayani (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
Analyzing the effect of Working Capital Turnover and Sales Growth on Profitability in Food and Beverages companies operating in the food and beverages sector and listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period is the aim of this research. Working Capital Turnover and Sales Growth are independent variables in this reserch while Profitability is used as the dependent variable. To process the data collected from quantitative research using the panel data regression analisis method, the author used the Eviews 9 application. Secondary data originating from financial reports published in full by the campany and which have been audited were taken by the author using a purposive sampling method via the official BEI website and the official website of the campany the author chose to be the sample. Data collected by the author resulted in a sample of 21 companies over a 3 year period, so that the sample data obtaines was 63 sample data. The test results by the author show that the Working Capital Turnover variable partially has on effect on Profitability, while Sales Growth partially has an effect on Profitability.